Uji Testing Kualitas Website Pemerintah Daerah Dengan GTMETRIX - Teresa Irmina Nangameka; Eriza Erfiana Amir (Institut Pemerintahan Dalam Negeri (IPDN) Kampus Sumatera Barat, 2023)
Website is the primary tool to see the level of e-government implementation. Website quality as a form of e-government is crucial in improving public services and government transparency. One way of realizing e-government is by creating a competitive environment to test developments in information technology. This research is aimed at measuring and comparing the quality level of the official websites of the 4 (four) Regional Governments that are the focus of the study, including Situbondo, Jember, Bondowoso and Banyuwangi Regencies and providing recommendations for improvements based on the evaluation results. The method used is the Automated Usability Testing Tools method on the home page of the Regional Government website. The test tool used is GTMetrix, which checks website speed, performance, and durability. The Automated Usability Testing Tools method measures website performance with high accuracy. Testing was carried out for 10 (ten) working days, with the GTMetrix indicators tested in this research being Performance Score, Structured Score, Page Load Time, Largest Contentful Paint, Total Blocking Time, and Cumulative Layout Shift. The results of this test by GTMetrix placed Bondowoso Regency at the top in website optimization compared to the other three official regional government sites. Specifically, the Bondowoso Regency website got the highest score for the Performance Score indicator, and then for the Structured Score indicator, the Situbondo Regency website took the lead. Furthermore, the Bondowoso Regency website is the fastest for the Page Load Time indicator. Largest Contentful Paint, as the next indicator, places the Bondowoso Regency website as the most immediate to load significant content or elements on its website. Then, in Total Blocking Time, between the Situbondo and Bondowoso Regency websites, packing a small scope on the website's home page display requires little time. Finally, the Bondowoso and Banyuwangi Regency websites received a Good or Good score for the Cumulative Layout Shift. The findings of this evaluation are essential in addition to providing valuable insights for improving the quality of e-government services in the study area and increasing the accessibility and efficiency of services to the community.